Surgical outcomes of vitrectomy in patients with complications of diabetic retinopathy at a tertiary care center - sultan, sharjeel; Shakeel, Ayisha; Khanzada, Mahtab Alam; Zaman, Yawar; Kamil, Zeeshan; Waris, Nazish (Journal of Liaquat University of Medical & Health Sciences, 2021)
OBJECTIVE: Surgical outcomes of vitrectomy in patients with complications of diabetic retinopathy in a tertiary care center. METHODOLOGY: In this prospective, observational, interventional study, the fifty eyes underwent pars plan vitrectomy (PPV) for complications of proliferative diabetic retinopathy (PDR) from January to September 2019. The visual success for patients who underwent PPV was determined by the estimation of best-corrected visual acuity (BCVA) and central macular thickness (CMT) during the follow-up period. Statistical package for social science (SPSS) version 20 was used for data analysis. RESULTS: In this study, 86% of eyes achieved BCVA of better than 20/200. The common complication was an iatrogenic break (20%) during a surgical procedure; other complications include increase intraocular pressure (20%), hypotony (12%), and postoperative vitreous hemorrhage (14%). The use of intraoperative anti-VGGF was found to reduce intra-operative and recurrent vitreous hemorrhage with good visual outcomes. CONCLUSION: Despite medical advances in the management of patients with diabetes, mixed-gauge vitrectomy remains essential for visual rehabilitation of selected patients with non-clearing VH and tractional complications of PDR, and the use of AVEGF pre and postoperative enhance our ability to achieve the good visual outcome. KEYWORDS: Vitrectomy, Intravitreal anti-VEGF, PDR complications, 23 G, 25 G, 27 G.